Euro Theoretical study of acetylation of ethanol catalyzed by Mn2+ ions - Caglieri, Silvana (Journal of Clinical & Experimental Toxicology, 2020)
A theoretical study of acetylation of ethanol catalyzed by Mn 2+ ions from the analysis of intermediate of the reaction was carried out. The study of acetylation of alcohols is of great interest by the utility of its products of reaction and is one of the most frequently used transformations in organic synthesis as it provides an efficient means for protecting hydroxyl groups in a synthetic process. Acetylation of alcohols is a nucleophilic substitution reaction. This reaction can be catalyzed by Lewis acid, metallic ion. In reaction mechanism, the metallic ion formed a complex with the oxygen of the acetic anhydride carbonyl, facilitating the polarization of the same and the successive addition of alcohol at the position to form a tetrahedral intermediate, determining step of the rate of the reaction. Experimental studies were carried out and agreed that this reaction takes place with the formation of a tetrahedral intermediate. In the present theoretical work were investigated the structure and energy of the tetrahedral intermediate of the reaction catalyzed by Mn 2+ ions. Geometries of all species involved in the acetylation were made and identified. All of the geometry optimizations were performed by the method at the DFT/B3LYP level of theory and were adopted the 6-31+G* basis sets. Energies were calculated using the Mechanics-UFF method. Following the same procedure it was identified the geometric parameters and energy of reaction intermediate. The calculations show 65.39 kcal/mol of energy for the tetrahedral intermediate and the energy of activation for the reaction was 26.29 kcal/mol. Acetylation is one of the most significant responses in natural blend since acetyl gatherings can be advantageously used to secure a wide scope of utilitarian gatherings including alcohols, amines, phenols, and thiols, among others .Acetylation with acyl halides or corrosive anhydrides has been accounted for utilizing either homogeneous or heterogeneous corrosive impetuses or on the other hand base impetuses .In this manner, a wide scope of homogeneous progress metal based or on the other hand organocatalysts have been created for the acetylation of alcohols utilizing RuCl3 , CeCl3 ,ZrCl4 , La(NO3)·6H2O, Al(OTf)3 ,AgOTf Co(II)salen complex NiCl2 Moreover, acetylation has additionally been accounted for with a progression of heterogeneous impetuses, for example, ionic fluids. Ethanol utilization is as of now the fourth most noteworthy preventable reason for death in the United States and is an extreme general wellbeing concern. Besides, ethanol is a huge hepatotoxicant and oxidative pressure assumes a focal job in the pathogenesis of alcoholic liver illness (ALD) Oxidative pressure is characterized as an unevenness between ace oxidants and enemies of oxidants, coming about in dysregulated redox flagging and control. This persevering oxidative unevenness can adjust redox delicate pathways and can bring about harm to cell macromolecules, including lipids, proteins and DNA, when receptive oxygen species are in abundance Explaining cell systems of adjusted hepatic redox homeostasis because of ethanol digestion is fundamental to understanding the commencement and movement of ALD.
Keywords: acetilation of alcohols; Mn2+; nucleophilic substitution reaction